2023
DOI: 10.1002/mas.21853
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of triacylglycerol and phospholipid sn‐positional isomers by liquid chromatographic and mass spectrometric methodologies

Abstract: Analysis of triacylglycerol (TG) and phospholipid sn‐positional isomers can be divided into two main categories: (a) direct separation by chromatography or other means such as ion mobility mass spectrometry and (b) quantification of regioisomer ratios by structurally informative fragment ions with mass spectrometric methods. Due to long retention times and limited performance, researchers are moving away from direct chromatographic separation of isomers, using mass spectrometry instead. Many established analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…Currently, we use ammonium acetate in the mobile phase as an additive, leading to the formation of ammoniated TAG ions [M + NH 4 ] + . Ammonium ions are the most widely used complexing agent for TAG regioisomer analyses across different studies . However, a recent study suggested that [M + NH 4 ] + ions might not be the ideal adduct type for establishing a fragmentation model, as the fragment ion ratios of different ACN:DB combinations are not predictable, and sodiated [M + Na] + adducts might be more suitable for creating a general fragmentation model .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, we use ammonium acetate in the mobile phase as an additive, leading to the formation of ammoniated TAG ions [M + NH 4 ] + . Ammonium ions are the most widely used complexing agent for TAG regioisomer analyses across different studies . However, a recent study suggested that [M + NH 4 ] + ions might not be the ideal adduct type for establishing a fragmentation model, as the fragment ion ratios of different ACN:DB combinations are not predictable, and sodiated [M + Na] + adducts might be more suitable for creating a general fragmentation model .…”
Section: Resultsmentioning
confidence: 99%
“…Ammonium ions are the most widely used complexing agent for TAG regioisomer analyses across different studies. 42 However, a recent study 43 suggested that [M + NH 4 ] + ions might not be the ideal adduct type for establishing a fragmentation model, as the fragment ion ratios of different ACN:DB combinations are not predictable, and sodiated [M + Na] + adducts might be more suitable for creating a general fragmentation model. 43 Contrary to the findings of Makarov et al, we have established an accurate fragmentation model using [M + NH 4 ] + adducts using two different triple quadrupole instruments (Shimadzu LC-MS 8045 and Waters Quattro Premier) used in this and a previous study.…”
Section: Resultsmentioning
confidence: 99%
“…Six isobaric tags were made to 83.8% purity and 90.9% isotopic purity using selective placement of six total isotopes on either the quaternary amine (balancer as the neutral loss) or on the chain (constant mass reporter ion). 53 Deuterium and 15 N were used to generate the appropriate sixplex isobaric tags. The majority of the isotopic impurity is due to the <100% purity of the starting material, which is almost entirely nonisotopic.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The 15 N-containing tags were synthesized by a Gabriel synthesis. Phthalimide- 15 N potassium salt was mixed 2:1 with 0.5 g of dibromopropane isotopologes, followed by mono-Boc protection of the resulting diamine. 31,39 The protected diamines were methylated by (HCHO isotopologes), followed by reductive amination.…”
Section: Reagents Andmentioning
confidence: 99%
See 1 more Smart Citation